Molecular weights and optimum temperature and pH for pepsin activity of three sciaenid finfish species from the Gulf of California - Perez-Velazquez, Martin; Maldonado-Othón, Carlos A.; González-Félix, Mayra L. (Archives of Biological Sciences, 2024)
Paper description: Byproducts from the processing of finfish from fisheries and aquaculture are often discarded. However, the enzymatic content of viscera has potential biotechnological and industrial applications. The molecular weights and optimum temperature and pH for pepsin activity from the sciaenids Cynoscion othonopterus, Cynoscion xanthulus, and Cynoscion parvipinnis were determined. Pepsins from the three species compare closely with pepsins from other fish in terms of molecular weight, with some variations in temperature and pH optima. Pepsins from othonopterus, C. xanthulus, and C. parvipinnis may have similar applications as other fish pepsins. Abstract: By-products from finfish processing from fisheries and aquaculture are often discarded. However, the enzymatic content of viscera has potential biotechnological and industrial applications. Such is the case for the sciaenids Cynoscion othonopterus, Cynoscion xanthulus, and Cynoscion parvipinnis, which are food and game fishes from the Gulf of California and whose viscera are commonly discarded after fish dressing. In this study, optimum temperature and pH for activity, as well as molecular weights of pepsin from the stomach of C. othonopterus, C. xanthulus, and C. parvipinnis were evaluated for the first time. Pepsin molecular weights were 30, 32.1, and 32.3 kDa, respectively. The highest activity of pepsin against hemoglobin was recorded between 40 and 45ºC for C. othonopterus and C. xanthulus and at 40°C for C. parvipinnis. The optimum pH was 2.0 for the three sciaenids. Biochemical characteristics were comparable to pepsins from other marine and freshwater fish species, so they could likely be used in some processes using this enzyme, like collagen extraction, fish silage production, or fish processing, among others.